Comparison of multiple arterial grafts vs. single arterial graft in coronary artery bypass surgery: a systematic review and meta-analysis - Ding, Qiuju; Zhu, Qingqing; Lu, Lichong; Cheng, Xiaofeng; Ge, Min (Frontiers in Cardiovascular Medicine, 2025)
Observational studies and randomised controlled trials (RCTs) have yielded conflicting results regarding the outcomes of multiple arterial grafts (MAG) vs. single arterial grafts (SAG) in coronary artery bypass graft (CABG) surgery. We conducted a comprehensive search across multiple databases for RCTs that directly compared MAG and SAG. The clinical outcomes assessed included all-cause mortality, cardiac-specific mortality, myocardial infarction (MI), repeat revascularization, stroke, sternal wound complications, and major bleeding. Outcomes were measured using hazard ratios (HR), relative risks (RR), and the corresponding 95% confidence intervals (CI). Eighteen RCTs involving 10,143 patients were included in the analysis. The follow-up period ranged from 6 months to 12.6 years, and the average age of the patients across the studies ranged between 56.3 and 77.3 years. MAG and SAG did not differ significantly in terms of the incidence of sternal wound complications, major bleeding, or stroke following CABG. However, the MAG group demonstrated a lower risk of all-cause mortality, cardiac mortality, MI, and repeat revascularization compared with the SAG group. MAG was associated with higher survival, lower risk of MI, and fewer repeat revascularization. Nonetheless, there were no significant differences in the incidence of sternal wound infections, major bleeding, and stroke between MAG and SAG.